Analysis on the Triaxial Shear Behavior and Microstructure of Cement-Stabilized Clay Reinforced with Glass Fibers. (26th November 2020) - Ruan, Bo; Zheng, Shilong; Teng, Jidong; Ding, Hui; Ma, Chao
Abstract : A series of triaxial compression tests were conducted to investigate the influence of the fiber content and confining pressure on the shearing characteristics of cement-stabilized clay reinforced with glass fibers. The glass fiber contents were 0, 1‰, 2‰, 3‰, and 4‰ by weight of the dry soil. The stress strain and volume change behavior, shear strength, and energy absorption of the test specimen were obtained. The results indicate that the inclusion of glass fibers can increase the shear strength, inhibit the volumetric dilation of the test specimen, and improve its brittle behavior. The cohesion of the cement-stabilized clay reinforced with 4‰ glass fiber content is 2.8 times greater than that of the cement-stabilized clay. The effect of the fiber content on the friction angle is not obvious. It is found that the glass fiber reinforcement is more substantial under a low confining pressure. The scanning electron microscopy test results show that the surface of the glass fiber is wrapped with cement hydrate crystals, which increases the bite force and friction between the fiber and the soil particles. A single fiber is similar to an anchor in the soil, which enhances the mechanical properties of the cement-stabilized clay reinforced with fibers.